Root Extracts From Ononis spinosa Inhibit IL-8 Release via Interactions With Toll-Like Receptor 4 and Lipopolysaccharide - Spiegler, Verena; Gierlikowska, Barbara; Saenger, Thorsten; Addotey, John N.; Sendker, Jandirk; Jose, Joachim; Kiss, Anna K.; Hensel, Andreas (Frontiers in Pharmacology, 2020)
Extracts from the roots of Ononis spinosa L. (restharrow roots) are traditionally used for the treatment of patients with urinary tract infections due to its mild diuretic activity, caused by the inhibition of renal human hyaluronidase-1 by isoflavonoids. Preliminary studies also indicated antiinflammatory effects. The following study aimed at investigating potential anti-inflammatory effects of restharrow extracts, prepared with solvents of different polarity. A dichloromethane extract (OS1), mainly composed of isoflavonoids and triterpenes as characterized by LC-MS, showed a concentration-dependent (25–100 μg/mL) inhibition of IL-8 and TNF-α release from LPS-stimulated human neutrophils. Significant inhibition was also found for the triterpene α-onocerin and the norneolignan clitorienolactone B, isolated from OS1. Further, OS1 and both compounds significantly decreased the expression of the adhesion molecules CD11b/CD18 and conversely increased the expression of CD62L in LPS-stimulated human neutrophils. This finding corresponds to a reduced inflammatory response by the inhibition of adhesion and migration of immune cells. As all of the observed effects are potentially mediated via Toll-like receptor 4 (TLR4) signaling, TLR4 transfected HEK293 cells were incubated with OS1. LPS-induced IL-8 secretion was significantly inhibited in a concentration-dependent manner, confirming TLR4 antagonism. This inhibition, however, was in part caused by an interaction of OS1 with LPS. In addition, also an aqueous extract containing high amounts of isoflavonoid glycosides and saponins from the roots of O. spinosa showed anti-inflammatory effects by interacting with the TLR4 signaling pathway. This study rationalizes the traditional use of extracts from O. spinosa for therapy of urinary tract infections, due to its potential anti-inflammatory effects that are mediated via TLR4 receptor antagonism.